Case Report: Gold Miner’s Lung: A Case of Chronic Hypersensitivity Pneumonia in Amazonian Forest - Aissaoui, Houari; Chaptal, Milene; Thomas, Vincent; Louvel, Dominique; Adenis, Antoine; Drak Alsibai, Kinan (Frontiers in Tropical Diseases, 2021)
The hostile conditions at informal and illegal mining sites in the Amazonian forest erode the miner’s health, exposing workers to a broad range of diseases because most of the gold is extracted using mercury (Hg). The Hg vapor used daily at gold panning sites presents an environmental threat to the ecosystems and human health. We report the case of a 58-year-old man who has worked in gold panning for over 30 years, presented with diffuse interstitial pneumonia characterized by bilateral images of ground glass and mosaic opacities on the chest CT scan. Based on the negative differential diagnosis (cardiovascular, infectious, autoimmune or cancer), the context of chronic exposure to Hg in a patient who has been working for decades on illegal gold panning sites, we concluded to a chronic form of heavy metal hypersensitivity pneumonia. This hypothesis was supported by high levels of mercury in blood and urine. Mercury hypersensitivity pneumonia might be more frequent than presently thought with thousands of workers chronically exposed to high mercury concentrations among others pollutants. Medical practitioners should systematically seek for chronic respiratory illnesses associated with pollutants exposure in these vulnerable workers with poor health.